Golf Club Rental and Inventory System (G-CRIS) / Mazita Mohamad - Mohamad, Mazita (2016)
Golf Club Rental and Inventory System (G-CRIS) is an online web based system. Currently they are using manual process to manage their business activities. The customer also need to register manually to be a member or to rent any equipment or venue provided by them. The model used for G-CRIS system is Prototype Model which has Requirement Gathering, Quick Design, Building Prototype, User Evaluation, Refining Prototype and Engineer Product. Besides that, system testing plan and evaluation from user and experts acts as a method to improve the functionality, usability and interface design of the system. The system has been tested by three (3) expert and thirty (30) respondents. The mean is 4.23 for perceived usefulness with standard deviation of 0.530 has been achieved for the satisfaction construct. It is hoped that G-CRIS will provide the best solution to manage the problem faced by GCDD organization.